2019
DOI: 10.1186/s12879-019-3952-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of Zika virus transmission in the community of Puerto Plata, Dominican Republic

Abstract: Background Zika virus is associated with increased cases of both microcephaly and Guillain-Barré syndrome. Community knowledge, perceptions and practices to prevent infection with the Zika virus are not well understood, particularly among high risk populations living in resource-poor and Zika-endemic areas. Our objective was to assess knowledge of symptoms, health effects and prevention practices associated with Zika virus in rural communities on the northern coast of the Dominican Republic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
6
11
0
2
Order By: Relevance
“…This was also consistent with findings from prior studies [33,35,36]. This reinforces the need for comprehensive educational campaigns and widely available information [37], appropriate to the social cultural condition of target population [20,38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was also consistent with findings from prior studies [33,35,36]. This reinforces the need for comprehensive educational campaigns and widely available information [37], appropriate to the social cultural condition of target population [20,38].…”
Section: Discussionsupporting
confidence: 90%
“…The use of condoms to prevent transmission of ZIKV during sexual intercourse was infrequently used in our population. Consistent with prior studies [ 32 , 34 , 37 , 39 ], condom usage for a reason other than contraception is understandably unpopular. Being a participant in a stable union was associated with the absence of condom usage, repeating findings from another Brazilian study [ 43 ].…”
Section: Discussionsupporting
confidence: 76%
“…Our findings reveal very low awareness among ZIKV infected women about the sexual route as a mode of transmission of ZIKV, and those women who had this information did not use condoms because they did not understand the reasons underlying the use of this measure, as the fetus was already developing. These results are aligned with other studies where sexual transmission was known by fewer than half of participants [ 12 , 24 , 35 ] and an analysis of the news published in the U.S.A. that revealed that almost all publications (96.8%) mentioned mosquitoes as a transmission route, but just over a half cited the sexual transmission of ZIKV (55.3%) [ 36 ]. A knowledge, attitudes and practices (KAP) analysis with American travelers concluded that knowledge of the sexual transmission of Zika significantly increases the odds of using condoms, thus improving targeted messaging through media may increase awareness and the use of preventive measures [ 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…Reproductive rights and pregnancy decision-making are the topics that are closely tied to religious and other cultural factors that limit access to contraception, which was highly recommended during the ZIKV outbreak [ 34 , 35 ]. Research suggests that knowledge of the sexual transmissibility of ZIKV significantly increases the odds of taking a preventive action against the infection, especially condom use or sexual abstention [ 36 ]. Borges et al in their Brazilian study reported that there were missed opportunities for prevention of perinatal transmission of the virus through behavioral change, including effective contraception to prevent pregnancy and condoms to prevent perinatal transmission, as a complement to vector control [ 37 ].…”
Section: Discussionmentioning
confidence: 99%